Design of a Walkway Using Renewable Energy Harvesters Within Pavement - Maghsoudi Nia, E. (Springer Science and Business Media Deutschland GmbH, 2021)
Generally, pedestrian walkway are designed to provide an accessible and safe path for people who prefer to walk. The walking activity can benefit both people and society in term of health and environment conservation through reducing usage of vehicle transpiration. Hence, the pedestrian walkway can serve more than providing a safe path and are potential to be a pedestrian and environmentally friendly walking space. This study aims to design a pedestrian and environmentally friendly walkway. The results of experiment results showed that 48.88 kWh energy is produced by pedestrian footsteps and synthetic rubber can provide an ergonomic pavement for pedestrian. Hence, the study is contributed in developing environmentally friendly walkway using renewable energy system as the contributor factor in reducing fossil fuel consumption of urban spaces sector. Moreover, merging pedestrian friendly walkway with hybrid renewable energy technologies (for generating electricity of lighting and providing usersâ comfort as well) would develop green concepts for pedestrian paths in cities. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.